1115 Undertreatment of vascular risk factors in patients presenting with ischaemic ocular events: results from 395 patients in a tertiary centre. (1st December 2017) - Zarkali, Angeliki; Cheng, Amanda; Dados, Agnes; Simister, Rob; Chandratheva, Arvind
Abstract : Introduction: Ocular events are considered lower risk than other transient ischaemic attacks (TIA). We aimed to determine recurrence risk, prevalence and management of vascular risk factors. Setting: University College Hospital London daily TIA-clinic, main referral centre for North-Central London. Consecutive records for all patients with transient/permanent ischaemic visual loss reviewed, January 2014-September 2016. Results: Of 395 patients, mean age 64 years (SD=15.1), 261 (66%) had transient and 134 (34%) permanent events. 51.1% had hypertension, 34.4% hypercholesterolaemia, 14.7% diabetes, 10.9% ocular events, 10.1% ischaemic heart disease (IHD), 7.1% atrial fibrillation (AF), 6.3% TIA, 5.1% stroke, and 12.4% were smokers. Median risk factors was 1 (range 1–6), but 88 (22.3%) had ≥3. Permanent visual loss was more common in patients with previous IHD (p<0.001), TIA (p<0.001), ocular events (p<0.001), diabetes (p=0.032), hypertension (p<0.001) and smokers (p=0.077). 90 day recurrence was 10.1%, higher (14.8%) in patients with ≥3 risk factors (HR=1.67, 95%CI=[0.89–3.09], p=0.120). Secondary prevention was better in patients with past TIA than those with ocular events; 60% vs 45% received antiplatelets and 92% vs 51% statins. Only 16 (51.6%) with known AF were anticoagulated, despite all having CHADSVASC≥1. Conclusion: One-fifth of patients with ocular events had ≥3 risk factors; these had higher recurrences. Only half of patients with previous ocular events were on antiplatelets/statins. These patients should be investigated and treated as aggressively as other TIA/strokes.